The use of herbal preparations as topical therapy during pre- and post-surgery in patients with 3–4 grade hemorrhoids - S. V. Vasiliev; A. I. Nedozimovanii; D. E. Popov; A. S. Vasiliev; I. V. Gor (Амбулаторная хирургия)
Introduction. The market presents a huge amount of topical preparations, which manage the clinical manifestations of hemorrhagic disease, and there is also no shortage of means that affect post-operative pain. However, there is no single consensus of patient management in the preoperative period, and there is no generally recognized protocol for the treatment of pain after hemorrhoidectomy.Aim. To determine the effectiveness of using Fleming’s ointment during pre- and post-surgery in patients with 3–4 grade hemorrhoids.Material and methods. 85 patients with a diagnosis of hemorrhoids III–IV grade were divided into 2 groups. The Milligan-Morgan’s hemorrhoidectomy using standard electrocoagulation methods under intravenous anesthesia was performed in all patients. Fleming ointment was used as a topical agent for 2–3 weeks before the operation and for 2.5 weeks after the operation in Group A (43 patients). In group B (42 patients), depending on the prevalence of symptoms, suppositories with phenylephrine, lidocaine, local, hormonal ointments were used, also Liniment Levomekol was used as a local therapy after surgery in the group B. The results were evaluated according to the following criteria: Pain level, symptoms’ degree of the disease against the background of the use of local agents was evaluated by VAS. The multiplicity of the introduction of NSAIDs in 2 groups was considered. The adequacy of the wound healing correlated with the duration of maintaining inflammation in the wound, we also considered the daystay and days of disability.Results. Pain level according to VAS on the 1, 3, 7, 12 days after surgery in patients from group A is 0,6 points lower than in patients from group B. The average number of NSAIDs intake in the postoperative period in Group A was 1,4 times less than in Group B. There was no significant difference in wound reaction, day-stay and days of disability. The symptoms of hemorrhoids, estimated by VASh, were significantly less pronounced in patients who used Fleming ointment (see table 0)Conclusions. Fleming ointment can be recommended as an adequate topical agent in the perioperative management of patients with 3–4 grade hemorrhoids.